2021
DOI: 10.24036/10778171074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hots-Oriented Worksheets on Heat and Kinetic Theory of Gases on Students' Critical and Creative Thinking Ability with Guided Inquiry Model in Grade XI SMA Al-Istiqamah Pasaman Barat

Abstract: This research aims to see how effect of HOTS-oriented worksheets on heat and kinetic theory of gases on students' critical and creative thinking ability with guided inquiry model in grade XI SMA Al-Istiqamah Pasaman Barat. The type of research used is quasi-experimental. In this research, two classes were used as the sample class, where class XI IPA 1 was the experimental class and class XI IPA 2 was the control class. The difference in treatment between the two classes is that in the experimental class the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…If learning is well collaborated between learning resources and learning models in a learning environment, then the quality of the learning process will increase [22]. CTL, also known as problembased instruction, is a teaching method that employs real-world situations to teach students critical thinking and problem-solving abilities, as well as subject-specific knowledge and concepts.While the scientific approach is a learning process centered on students to stimulate intellectual development (thinking skills) so that it is appropriate for them observing, establishing problems, formulating hypotheses, gathering data using various methodologies, evaluating data, drawing findings, and communicating to construct concepts, laws, or principles them, the scientific approach is a learning process centered on students to stimulate intellectual development (thinking skills) so that it is relevant for them to construct concepts, laws, or principles through observing, formulating problems, formula [13].…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If learning is well collaborated between learning resources and learning models in a learning environment, then the quality of the learning process will increase [22]. CTL, also known as problembased instruction, is a teaching method that employs real-world situations to teach students critical thinking and problem-solving abilities, as well as subject-specific knowledge and concepts.While the scientific approach is a learning process centered on students to stimulate intellectual development (thinking skills) so that it is appropriate for them observing, establishing problems, formulating hypotheses, gathering data using various methodologies, evaluating data, drawing findings, and communicating to construct concepts, laws, or principles them, the scientific approach is a learning process centered on students to stimulate intellectual development (thinking skills) so that it is relevant for them to construct concepts, laws, or principles through observing, formulating problems, formula [13].…”
Section: B Discussionmentioning
confidence: 99%
“…Understanding, mastery of the material and student achievement are indicators of the success of the physics learning process [12]. In the appearance of the media, the teacher only provides an explanation of the material, causing the learning process that takes place to be dominated by the teacher [13]. So, learning physics is very important because it can foster higher thinking skills, especially critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…The population is a generalization area consisting of objects or subjects that have certain qualities and characteristics determined by the researcher to be studied and then drawn conclusions [8]. The population of this study is all the questions for the Mid-Semester Examination and the Physics Semester Exam used in high schools in Agam district in the 2018/2019 and 2019/2020 school years.…”
Section: Methodsmentioning
confidence: 99%
“…Instruments are tools used to approach the research objectives. The research instrument is a tool used to measure the observed natural and social phenomena [11]. The research instrument used is compiled and will be tested for validity.…”
Section: Methodsmentioning
confidence: 99%